2022
DOI: 10.1007/s10865-021-00270-6
|View full text |Cite
|
Sign up to set email alerts
|

Hesitant but vaccinated: assessing COVID-19 vaccine hesitancy among the recently vaccinated

Abstract: We administered a survey during the fifteen-minute wait time after the COVID-19 vaccine was given (N = 1475) to examine attitudes towards COVID-19 vaccines among adults who were vaccinated in Arkansas between April 22nd and July 6th, 2021. We found 60% of those who had just been vaccinated reported some level of hesitancy, including 10% who reported being “very hesitant.” Hesitancy was not evenly distributed across sociodemographic groups (age, sex, race/ethnicity, and education) and was associated with whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 30 publications
7
37
0
Order By: Relevance
“…The phenomenon of the 'vaccinated but hesitant' is well described [26]. In one US study, 60% of recently COVID-19 vaccinated individuals expressed some level of hesitancy [27]. Conversely, motivations toward vaccination may not convert to vaccine uptake.…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon of the 'vaccinated but hesitant' is well described [26]. In one US study, 60% of recently COVID-19 vaccinated individuals expressed some level of hesitancy [27]. Conversely, motivations toward vaccination may not convert to vaccine uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Arce et al, 2021 , Brown et al , Carson, 2021 , Chen and Krieger., 2021 , Kazemian et al, 2021 , Latkin et al, 2021 , Liao and De Maio., 2021 , Liu and GabrielLi, 2021 , Mollalo and Tatar, 2021 , Phelan and Bruce, 2015 , Rane et al, 2022 , Salomon et al, 2021 , Siegel et al, 2021 , Tal et al, 2020 , Willis et al, 2022 , Wright et al, 2014 …”
Section: Uncited Referencesmentioning
confidence: 99%
“…A survey in April 2021 indicated that 52% of those reporting they would definitely not have the vaccine in November/December 2020 later accepted it when offered (and 15% of those not yet offered were likely to accept) [ 15 ], while another survey noted a reduction in hesitancy from 26.9% in October 2020 to 16.9% in January/February 2021 [ 23 ], indicating substantial shifts in preferences as the campaign has progressed. In the US, a survey revealed a high prevalence of some degree of hesitancy even among those being vaccinated (60%), with levels varying by age and ethnicity [ 24 ]. We found the probability of going from recorded as declining to being vaccinated was broadly similar across ethnic groups, but slightly higher in the South Asian population.…”
Section: Discussionmentioning
confidence: 99%